The Profile of Anthropometric Components and Aerobic Capacity of Male and Female Wrestlers: Profil Komponen Antropometri dan Kapasitas Aerobik pada Pegulat Pria dan Wanita - Bangbang Syamsudar; Nita Abadi Rahayu; Sony Hasmarita; Vicki Ahmad Karisman (Journal of Physical and Outdoor Education, 2022)
This study aims to describe the anthropometric component profile and aerobic capacity of male and female wrestlers in the West Bandung Regency. This study uses a descriptive method with a cross-sectional approach. The research sample used accidental sampling as many as 15 people consisting of 10 men and 5 women. The data collection technique was carried out by conducting tests and measurements of anthropometry and VO2max through the bleep test. The results showed that there was no significant difference in anthropometric measurements between male and female wrestlers (sig> 0.05), in the measurement of body mass index (BMI) results for male and female wrestlers, which were much lower than the ideal standard, in the VO2max measurement results for all samples ( 15 people) mostly (75%) were in the average category and only (27%) were in a good category. The last picture is that there is no significant correlation between Body Mass Index and aerobic capacity of male and female wrestlers